Mergers and Acquisitions: The Nigerian Banking Consolidation Program - Agu, Chukwuma (Universiti Utara Malaysia, 2011)
This paper examines the determinants of the exit behaviour of banks in the Nigerian consolidation program during July 2004 and December 2005. We conceptualise the exit process in a flexible bivariate competing risks model to examine the importance of macroeconomic and industry-specific factors for both merged banks and failed banks jointly. The preliminary results suggest that bank-specific characteristics mattered more for preventing bank failure than they did for emergence of the M&A banks. Second, the Central Bank of Nigeria’s assistance was highly influential in preventing bank failure, and, for banks that benefited, the assistance increased their probability of being merged or acquired. Also, we found no strong evidence suggesting that the prevailing macroeconomic conditions and industry-specific factors had influenced exit behaviour of banks during the consolidation exercise. We found evidence of structural dependence between failure and merger and acquisition hazards induced by CBN incentive.